Forest Conservation Base on Religious Values: A Case Study of Indigenous People of Kampung Dukuh - M. Rachmat Effendi; Edi Setiadi; Malki Ahmad Nasir (USIM Press, 2024)
Vol. 22 No. 2 (2020): Journal of Islamic Social Sciences and Humanities (Special Issue)